PENGARUH INTELLECTUAL CAPITAL, KUALITAS AUDIT, FINANCIAL DISTRESS, DAN AUDIT TENURE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Maisyaroh, Titin; Taufik, Taufeni; Badriyah, Nurul (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2025)
Financial reports used by stakeholders to make decisions must show the results of their decisions through the integrity of the financial reports. The integrity of financial reports means showing financial reports that are honest, reliable, and neutral. This study aims to determine and analyze the effect of intellectual capital, audit quality, financial distress, and audit tenure on the integrity of financial reports in financial companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The study population was all financial companies listed on the Indonesia Stock Exchange during the 2019-2021 period totaling 105 companies. Based on the purposive sampling method, the research sample was obtained amounting to 171 companies from 57 companies with a 3-year research period. Data analysis used statistical methods using the SPSS software program. The results of the study showed that intellectual capital, audit quality, financial distress, and audit tenure had an effect on the integrity of financial reports.